Post-translational modifications in heat stress-related diseases - Cui, Qi; Jia, Keran; Li, Fang; Zheng, Jie; Wang, Fukun (Frontiers in Molecular Biosciences, 2025)
Post-translational modifications (PTMs) act as pivotal molecular hubs integrating heat stress signals into cellular responses driving heat-related diseases like heatstroke. This review synthesizes evidence demonstrating that dynamic PTM networks—including phosphorylation, acetylation, ubiquitination, methylation, SUMOylation, and S-nitrosylation—orchestrate pathophysiology through three distinctive mechanisms: PTM crosstalk, tissue-specific PTM signatures defining organ vulnerability, and translational utility. The potentials of PTM alterations as novel biomarkers for early diagnosis/prognosis and PTM-targeted interventions as therapeutic strategies are discussed. By delineating how PTMs reconfigure proteostasis, metabolism, and inflammation, this review provides a mechanistic framework for targeting PTM pathways to mitigate heatstroke and related conditions.